Proteomic Changes to the Updated Discovery of Engineered Insulin and Its Analogs: Pros and Cons - Naeema Hanif; Hezhou Wu; Peizhou Xu; Yun Li; Amir Bibi; Asma Zulfiqar; Muhammad Zafar Iqbal; Muhammad Tahir; Xiangyang Zhang; Asif Ali (Current Issues in Molecular Biology, 2022)
The destruction of β-cells of the pancreas leads to either insulin shortage or the complete absence of insulin, which in turn causes diabetes Mellitus. For treating diabetes, many trials have been conducted since the 19th century until now. In ancient times, insulin from an animal’s extract was taken to treat human beings. However, this resulted in some serious allergic reactions. Therefore, scientists and researchers have tried their best to find alternative ways for managing diabetes with progressive advancements in biotechnology. However, a lot of research trials have been conducted, and they discovered more progressed strategies and approaches to treat type I and II diabetes with satisfaction. Still, investigators are finding more appropriate ways to treat diabetes accurately. They formulated insulin analogs that mimic the naturally produced human insulin through recombinant DNA technology and devised many methods for appropriate delivery of insulin. This review will address the following questions: What is insulin preparation? How were these devised and what are the impacts (both positive and negative) of such insulin analogs against TIDM (type-I diabetes mellitus) and TIIDM (type-II diabetes mellitus)? This review article will also demonstrate approaches for the delivery of insulin analogs into the human body and some future directions for further improvement of insulin treatment.